PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ( STUDI KASUS PADA SMARTPHONE SAMSUNG DI NEO KOMUNIKA) - Taopik Hidayat (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to find out how the product quality on Samsung smartphones in CV. Neo Komunika, how is the interest in buying a Samsung smartphone at CV. Neo Komunika, and how the influence of product quality on buying interest in Samsung smartphones at CV. Neo Communications. The research method used is the associative method with quantitative data types and ordinal scales. Respondents taken in this study were consumers of CV. Neo Komunika with a sample size of 68 people. And processing data obtained from questionnaires distributed and then tested using validity test, reliability test, simple correlation test, coefficient of determination test, and hypothesis testing using t test > t-table or 8,238 > 1,670, then Ho is rejected and Ha is accepted which means quality product (X) has a positive effect on buying interest (Y) on Samsung smartphones at CV. Neo Communications, with a strong correlation coefficient of 0.712 and a coefficient of determination of 50% and the remaining 50% is influenced by factors not examined. Thus, it can be concluded that product quality has a positive influence on buying interest in Samsung smartphones at CV. Neo Communications. In other words, if the quality of the product is improved, the buying interest will also increase.